2020
DOI: 10.1097/01.ogx.0000723728.09046.e3
|View full text |Cite
|
Sign up to set email alerts
|

The WOMAN Trial: Clinical and Contextual Factors Surrounding the Deaths of 483 Women Following Post-Partum Hemorrhage in Developing Countries

Abstract: Background: Post-partum haemorrhage (PPH) is a leading cause of maternal death worldwide. The WOMAN trial assessed the effects of tranexamic acid (TXA) on death and surgical morbidity in women with PPH. The trial recorded 483 maternal deaths. We report the circumstances of the women who died. Methods:The WOMAN trial recruited 20,060 women with a clinical diagnosis of PPH after a vaginal birth or caesarean section. We randomly allocated women to receive TXA or placebo. When a woman died, we asked participating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…However, this should be done as part of an overall health system strengthening strategy focused on curbing maternal death and disability. As shown by a secondary analysis of the WOMAN trial, which examined the deaths of 483 women following PPH, other clinical and contextual factors should be tackled, including maternal anemia, delayed referral to higher levels of care, unavailability of blood transfusion, and poor facility infrastructure [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this should be done as part of an overall health system strengthening strategy focused on curbing maternal death and disability. As shown by a secondary analysis of the WOMAN trial, which examined the deaths of 483 women following PPH, other clinical and contextual factors should be tackled, including maternal anemia, delayed referral to higher levels of care, unavailability of blood transfusion, and poor facility infrastructure [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the study was an abstract – hence we cannot fully evaluate methods and study quality – and the unit cost of tranexamic acid ($187) was significantly higher than other studies ($5.60 to $50.40) which may have affected the findings. The study used data from WOMAN trial, where most (91.6%) of the study participants were from Africa and Asia 28 with higher rates of maternal mortality and more limited health resources compare to the US context.…”
Section: Discussionmentioning
confidence: 99%
“…Through this pro-hemostatic mechanism, TXA reduces bleeding, but it may also increase the risk of thromboembolic events. Recently published randomized clinical trials (RCTs) in trauma and other patient populations have not reported an increased risk of symptomatic thromboembolic events, [4][5][6][7][8] except for one trial in patients with gastrointestinal bleeding. 9 However, some retrospective observational studies have reported an association between TXA use and thromboembolic events in severely injured patients, while others have not.…”
Section: Introductionmentioning
confidence: 99%
“…3 To reduce death from traumatic hemorrhage, tranexamic acid (TXA), an antifibrinolytic agent, is commonly administered in bleeding trauma patients, as large multicenter trials have demonstrated improved primary or secondary outcomes associated with TXA use, including survival. [4][5][6][7][8] TXA is a lysine analog that competitively inhibits the activation of plasminogen to plasmin, and at higher concentrations inhibits plasmin, thus decreasing fibrinolysis and increasing clot stability. Through this pro-hemostatic mechanism, TXA reduces bleeding, but it may also increase the risk of thromboembolic events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation